Art Deco : van de Basiliek van Koekelberg tot het Flageygebouw - Bertels, Inge, 1976-; Strauven, Francis, 1942- (Tielt : Lannoo, 2008)
Vorst, Elsene, Westende, Antwerpen, Charleroi, Schaarbeek, Deurne, Zonnebeke, Brussel, Bléharies, Sint-Gillios, Ukkel, Gent, Berchem, Antwerpen, Jette, Koekelberg, Kraainem, Sint-Jans-Molembeek, Sint-Genesiius-Rode, Heverlee, Sint-Niklaas, Elsene, Laken, DOornik, Charleroi, Beringen-Mijn
Keywords: Art deco